Early Islamic North Africa. A New Perspective, by Corisande Fenwick. - Nef, Ann Liese (Journal of Islamic Archaeology, 2021)
Early Islamic North Africa. A New Perspective, by Corisande Fenwick. Bloomsbury Publishing, 2020. 202pp., $90. ISBN-13: 9781350075184.